Reduction in Anger in Participants with Chronic Pain after a Mobile-Based Mindfulness Intervention - Vered Valeria Latman; Muhammad Abid Azam; Helia Ghazinejad; Amir Zarie; Fatma Al-Rubeye; Natasha Aguanno; Zahra Mohamedbhai; Myra Massey; Joel Katz (Taylor & Francis Group, 2019)
Introduction/Aim: To evaluate the effects of a novel 12-minute mobile-based mindfulness intervention on anger in participants with chronic pain, depression/anxiety and condition-free controls. Methods: Four groups of university students: n = 42 with chronic pain (CP+app), n = 39 with symptoms of depression/anxiety (DA+app), and 2 groups of condition-free controls (CF+app; n = 54 and CF-app; n = 26) completed the Anger subscale of the Profile of Mood States at baseline (pre) and after (post) a 12-min intervention, during which participants were instructed to pay attention to the flow of breath and press "breath" or "other" buttons on a smartphone at the sound of a tone. The CF-app group attended to their breath for 12 minutes without use of the smartphone app. Results: We used a 2-way ANOVA with Time (baseline, post-intervention) and Group (CP+app, DA+app, CF+app, CF-app) to evaluate Anger scores. The simple main effect of Group was significant at baseline, F(3,152) = 14.83, p < .001, ηp2 = .22, and post-intervention, F(3,152) = 9.57, p < .001, ηp2 = .15. At baseline, the CP+app and DA+app did not differ in Anger scores, which were significantly higher than CF+app and CF-app (p < .05). Post-intervention, anger levels for CP+app dropped to meet those of both CF+app and CF-app, while DA+app remained significantly higher than the rest (p < .05). Simple main effects of Time were significant for CP+app, F(1,152) = 27.90, p < .001, ηp2 = .15 and DA+app, F(1,152) = 15.06, p < .001, ηp2 = .09, but not for CF+pp or CF-app. Discussion/Conclusions: Research has shown that anger can lead to increased pain sensitivity and intensity; therefore regulating anger using mindfulness may be a desirable goal as part of CP treatment.